Pricing Modified Barrier Options Using the Bino-Trinomial Tree Model: A Strategy for Loss Minimization - Rahayu, Rima Aulia; Agustina, Fitriani; Sidarto, Kuntjoro Adji (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
A particular exotic option that is widely traded in the global financial market is the barrier option. Barrier options are attractive because they have a limit that must be reached to activate the option. These limits may be utilized by investors as a point of reference to minimize potential losses. Accordingly, the researcher attempts to use the bino-trinomial tree model as a new approach to minimize losses. The purpose of this study is to analyze the bino-trinomial tree model to provide investors with more flexible hedging experience. The bino-trinomial tree model is obtained by combining the trinomial tree model at the first stage, then the binomial tree model at a further stage. This analysis was conducted by calculating the type of knock-out european call options. The results demonstrate that this model can effectively, accurately and flexibly manage the complex options required by modern investors, including multi-step single moving barrier options and single window barrier options.